Credit risk Rating and Assessment - El Baamrani, Mohammed; Brůna, Karel, 1973-; Čermáková, Daniela; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
The author of the thesis has been discussing and reviewing credit risk and risk assessment by dealing with two credit risk models; CreditRisk + Model and KVM model which is an adopted version of the Merton model. Then focus on financial ratios used by broad number of users from different industries and applying some of them on factual case by nominating Chevron Corporation as the chosen company to assess the credit risk associated with it and analysis its consolidated financial statement, then discuss briefly the credit rating at certain extend and finally perform an overall evaluation to determine the financial situation of the elected corporation.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses